Analysis of Postoperative Gait, Hip Strength, and Patient-Reported Outcomes After OTA/AO 61-B and 61-C Pelvic Ring Injuries. Issue 9 (September 2022) - Dean, Chase S.; Nadeau, Jason; Strage, Katya E.; Tucker, Nicholas J.; Chambers, Lori; Worster, Kate; Rojas, David; Schneider, Gary; Johnson, Tony; Hunt, Kenneth; Parry, Joshua A.; Mauffrey, Cyril
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objectives: To examine clinical gait parameters, hip muscle strength, pelvic functional outcomes, and psychological outcomes after surgical fixation of OTA/AO 61-B and 61-C pelvic ring injuries. Design: Retrospective review identified 10 OTA/AO 61-B patients and 9 OTA/AO 61-C patients for recruitment who were between 1 and 5 years after pelvic fixation. Gait and strength assessments, and patient-reported outcome scores were performed/collected and analyzed. Setting: Outpatient clinical motion performance laboratory. Patients/Participants: Patients with OTA/AO 61-B and OTA/AO 61-C fractures who were between 1 and 5 years after pelvic fixation. Main Outcome Measurements: Hip strength, kinetics, and spatial–temporal outcomes; Majeed Pelvic Outcome Score; Short Form 36; Hamilton Anxiety/Depression Rating Scales. Results: There were no differences in age, body mass index, or time since definitive fixation between OTA/AO 61-B and 61-C groups. The OTA/AO 61-C group had higher median injury severity scores, longer length of stay, and greater postoperative pelvic fracture displacement. There was no difference in bilateral hip strength, bilateral peak hip moments, peak hip power, and walking speed between groups. Patients with OTA/AO 61-C fractures had lower scores on Short Form 36 General Health and Majeed Work, with a trend toward a lower Total Majeed score. There were no differences in self-reported total anxiety and depression symptoms. Conclusions: This study did not identify any gait, strength, or psychological differences between OTA/AO 61-B and 61-C injuries at 1–5 years of follow-up. However, increased injury severity in OTA/AO 61-C patients may have residual consequences on perceived general health and ability to work. This pilot study establishes a template for future research into functional recovery of patients with severe pelvic ring trauma. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.